2021
DOI: 10.1123/ijsnem.2020-0125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pragmatic Methods to Rapidly Assess Habitual Beverage Intake and Hydration Status in U.S. Collegiate Athletes

Abstract: Fluid intake recommendations have been established for the athletic population in order to promote adequate hydration. The Beverage Intake Questionnaire (BEVQ-15) is a quick and reliable food frequency questionnaire that quantifies habitual beverage intake, which has been validated in children, adolescents, and adults. However, no validated beverage consumption questionnaire is available for collegiate athletes. Urine color (UC), while feasible for determining hydration status, has not been validated within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the justification for these fluid amounts is difficult to discern and the prevalence of dehydration among collegiate athletes before practice still ranges from 65-75%. 10,16,35 Therefore, the purpose of this review was to identify current pre-exercise fluid recommendations and protocols and their sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the justification for these fluid amounts is difficult to discern and the prevalence of dehydration among collegiate athletes before practice still ranges from 65-75%. 10,16,35 Therefore, the purpose of this review was to identify current pre-exercise fluid recommendations and protocols and their sources.…”
Section: Discussionmentioning
confidence: 99%
“…Urine color has been established as a valid hydration assessment method within several populations, against urine osmolality and USG. [10][11][12] Researchers determined that euhydration, based on urine color is considered < 4 on the urine color chart. [13][14][15] Researchers using USG, through the use of a handheld refractometer, determined that euhydration for athletes could range from 1.018-1.020 when looking at 24hr USG samples and 1.024-1.026 for a first morning USG sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main reasons why wrestlers lose weight before the competition is that they have the psychology of thinking that the chance of medals is higher in a lower class and that the competition will contribute positively to them. However, considering the literature, studies on weight loss generally indicate that dehydration causes physical and physiological decline in athletes [4][5][6][7]. As there is a change in the hydration status of the athletes who lost weight before the competition, depending on the food and fluid restriction; It has been reported that symptoms such as sleep disturbance, memory, depression, learning, anxiety, body temperature irregularity and muscle function disorders can be observed [8].…”
mentioning
confidence: 99%